Globalization and environmental challenges : reconceptualizing security in the 21st century - Brauch, Hans Günter ; Úrsula Oswald Spring, Czeslaw Mesjasz, John Grin, Pál Dunay, Navnita Chadha Behera, Béchir Chourou, Patricia Kameri-Mbote, P. H. Liotta (Springer, 2017)
1141 p.